Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Interplay between colorectal cancer-related lifestyles and the gut microbiome: an exploratory analysis of metagenomic data - Rilla Tammi; Mirkka Maukonen; Niina E. Kaartinen; Kari Koponen; Teemu Niiranen; Guillaume Méric; Demetrius Albanes; Johan G. Eriksson; Pekka Jousilahti; Seppo Koskinen; Anne-Maria Pajari; Rob Knight; et al. (Cancer Causes & Control, 2026)
Purpose The gut microbiome may modify the associations between lifestyle factors and colorectal cancer (CRC) risk, but their complex interplay, including the interactions between lifestyle factors, remain underexplored. We examined associations between CRC-related lifestyle patterns and gut microbiome diversity and composition in Finnish adults. Methods Our data included 1,228 adults aged 25–64 years from the National FINRISK/FINDIET 2002 Study. Information on lifestyle and background factors was obtained through self-administered questionnaires. Dietary data were gathered using a 48-h dietary recall. CRC-related lifestyles were modelled using a CRC lifestyle index based on nine major risk factors for CRC. Lower index points reflected higher-risk lifestyles. The gut microbiome profiles were analyzed using shallow shotgun metagenome sequencing. Associations between the index and microbial diversity and composition were assessed using, e.g., linear regression and permutational multivariate ANOVA adjusted for relevant confounders. Results The index explained 0.2% of the variation in microbial composition between participants ( p < 0.05). Higher-risk lifestyles for CRC were associated with lower microbial diversity ( β 0.037, p 0.009). Higher-risk lifestyles were also associated with a higher relative abundance of species representing primarily the family Lachnospiraceae and genera such as Dorea and Mediterraneibacter , and lower relative abundance of species within the genus Bifidobacterium (< 0.0001). Conclusions Participants with higher- and lower-risk lifestyles showed clear differences in their gut microbiome diversity and composition, higher-risk lifestyles being associated with potentially adverse microbial traits. These findings contribute to identifying microbial features that may characterize early stages of CRC development in individuals with high-risk lifestyles.

Household environmental characteristics influence the house dust metagenome - Isabella Gamez; Farnaz Fouladi; Antonio Gonzalez; James Ward; Ziyue Wang; Laura E. Beane Freeman; Alison Motsinger-Reif; Shyamal D. Peddada; Rob Knight; Mikyeong Lee; Stephanie J. London (Environmental Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Classification of donkey systems in Ethiopia - Girma Birhan Asteraye; Ruth Jobling; Wudu T. Jemberu; Gina Pinchbeck; Theodore J.D. Knight-Jones; Rob Critchlow; Jonathan Rushton; Gemma L. Chaters (Preventive Veterinary Medicine, 2026)

ChIP provides 10-fold microbial DNA enrichment from tissue while minimizing bias - Shrikant Bhute; Jon G. Sanders; Se Jin Song; Sydney Lavoie; Austin Swafford; Caitlin Guccione; Lucas Patel; Antonio Gonzalez; Michelle G. Rooks; Rob Knight; Andrew Bartko (Molecular Biology Reports, 2025)
Background Host DNA depletion is a critical tool for accessing the microbiomes of samples that have a small amount of microbial DNA contained in a high host background. Of critical practical importance is the ability to identify microbial DNA sequences in frozen tissue specimens. Here, we compare four existing commercial methods and two newly introduced methods involving chromatin immunoprecipitation (ChIP) on frozen human and pig intestinal biopsies. Results We find that all methods that rely on differential lysis of host and microbial cells introduce substantial biases as assessed by 16 S rRNA gene amplicon profiling. However, ChIP enables 10-fold enrichment of microbial DNA while introducing less bias, sufficient to make assessment possible against background, in both pigs and humans. Conclusions We recommend ChIP in situations where host depletion is important but where minimizing taxonomic bias is essential, and the MolYsis or Zymo kit for situations where host depletion level is more important than taxonomic bias. Conclusions We recommend ChIP in situations where host depletion is important but where minimizing taxonomic bias is essential, and the MolYsis or Zymo kit for situations where host depletion level is more important than taxonomic bias.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Navigating diverse commercial fisher perspectives for effective knowledge exchange in fisheries research and management - Rob Hoschke; Natasha Pauli; Tim Langlois; Andrew T. Knight; Harriet Davies; Matt Navarro (Environmental Science & Policy, 2024)

Factors Influencing the Resilience of Created Tidal Marshes in the Fraser River Estuary, British Columbia - Daniel Stewart; Megan Lievesley; James E. Paterson; Daniel Hennigar; Robyn Ingham; Rob Knight; Brad Mason; Eric Balke (Wetlands, 2024)
More than 100 tidal marsh creation projects were constructed throughout the Fraser River Estuary, British Columbia, Canada from the 1980s to present. Past studies described and evaluated many of these projects and found varied success, but the underlying factors that determine project outcomes remain uncertain. Combining field sampling, spatial analysis, and statistical modeling of plant communities, we aim to address this knowledge gap by asking what factors influence the resilience of created marshes, as measured by (1) persistence of marsh vegetation, (2) native species dominance, and (3) species richness. We observed marsh recession in 40 of the 78 projects visited, representing 23,666 m 2 (9.3%) of the 254,357 m 2 of created marsh surveyed. Increases in mean site elevation had a negative effect on percent recessed area, while sites in the north branch of the river and sites further upriver were more prone to recession. From field observations and data interpretation we suggest that wake erosion and Canada Goose ( Branta canadensis ) herbivory may be drivers behind these losses and warrant further investigation. Dominance of native species declined with distance upriver, though invasive cattail ( Typha angustifolia, T. × glauca) defied this trend, dominating outer estuary sites, particularly closed embayments, when present. Native and non-native richness shared similar patterns and were comparable between reference and created marshes, increasing on average with elevation and distance upriver. These findings offer insight into how site design and location influence the outcome of marsh creation projects, and the challenges presented by stressors and environmental change in estuaries.

Predicting fungal infection rate and severity with skin‐associated microbial communities on amphibians - Melissa Y. Chen; Jordan G. Kueneman; Antonio González; Greg Humphrey; Rob Knight; Valerie J. McKenzie (Molecular Ecology, 2022)
Pathogen success (risk and severity) is influenced by host‐associated microbiota, but the degree to which variation in microbial community traits predict future infection presence/absence (risk) and load (severity) for the host is unknown. We conducted a time‐series experiment by sampling the skin‐associated bacterial communities of five amphibian species before and after exposure to the fungal pathogen, Batrachochytrium dendrobaditis ( Bd ). We sought to determine whether microbial community traits are predictors of, or are affected by, Bd infection risk and intensity. Our results show that richness of putative Bd ‐inhibitory bacteria strongly predicts infection risk, while the proportion of putative Bd ‐inhibitory bacteria predicts future infection intensity. Variation in microbial community composition is high across time and individual, and bacterial prevalence is low. Our findings demonstrate how ecological community traits of host‐associated microbiota may be used to predict infection risk by pathogenic microbes.

Impacts of the Marine Hatchery Built Environment, Water and Feed on Mucosal Microbiome Colonization Across Ontogeny in Yellowtail Kingfish, Seriola lalandi - Jeremiah J. Minich; Barbara Nowak; Abigail Elizur; Rob Knight; Stewart Fielder; Eric E. Allen (Frontiers in Marine Science, 2021)
The fish gut microbiome is impacted by a number of biological and environmental factors including fish feed formulations. Unlike mammals, vertical microbiome transmission is largely absent in fish and thus little is known about how the gut microbiome is initially colonized during hatchery rearing nor the stability throughout growout stages. Here we investigate how various microbial-rich surfaces from the built environment “BE” and feed influence the development of the mucosal microbiome (gill, skin, and digesta) of an economically important marine fish, yellowtail kingfish, Seriola lalandi , over time. For the first experiment, we sampled gill and skin microbiomes from 36 fish reared in three tank conditions, and demonstrate that the gill is more influenced by the surrounding environment than the skin. In a second experiment, fish mucous (gill, skin, and digesta), the BE (tank side, water, inlet pipe, airstones, and air diffusers) and feed were sampled from indoor reared fish at three ages (43, 137, and 430 dph; n = 12 per age). At 430 dph, 20 additional fish were sampled from an outdoor ocean net pen. A total of 304 samples were processed for 16S rRNA gene sequencing. Gill and skin alpha diversity increased while gut diversity decreased with age. Diversity was much lower in fish from the ocean net pen compared to indoor fish. The gill and skin are most influenced by the BE early in development, with aeration equipment having more impact in later ages, while the gut “allochthonous” microbiome becomes increasingly differentiated from the environment over time. Feed had a relatively low impact on driving microbial communities. Our findings suggest that S. lalandi mucosal microbiomes are differentially influenced by the BE with a high turnover and rapid succession occurring in the gill and skin while the gut microbiome is more stable. We demonstrate how individual components of a hatchery system, especially aeration equipment, may contribute directly to microbiome development in a marine fish. In addition, results demonstrate how early life (larval) exposure to biofouling in the rearing environment may influence fish microbiome development which is important for animal health and aquaculture production.

Major shifts in gut microbiota during development and its relationship to growth in ostriches - Elin Videvall; Se Jin Song; Hanna M. Bensch; Maria Strandh; Anel Engelbrecht; Naomi Serfontein; Olof Hellgren; Adriaan Olivier; Schalk Cloete; Rob Knight; Charlie K. Cornwallis (Molecular Ecology, 2019)
The development of gut microbiota during ontogeny is emerging as an important process influencing physiology, immunity and fitness in vertebrates. However, knowledge of how bacteria colonize the juvenile gut, how this is influenced by changes in the diversity of gut bacteria and to what extent this influences host fitness, particularly in nonmodel organisms, is lacking. Here we used 16S rRNA gene sequencing to describe the successional development of the faecal microbiome in ostriches ( Struthio camelus , n = 66, repeatedly sampled) over the first 3 months of life and its relationship to growth. We found a gradual increase in microbial diversity with age that involved multiple colonization and extinction events and a major taxonomic shift in bacteria that coincided with the cessation of yolk absorption. Comparisons with the microbiota of adults ( n = 5) revealed that the chicks became more similar in their microbial diversity and composition to adults as they aged. There was a five‐fold difference in juvenile growth during development, and growth during the first week of age was strongly positively correlated with the abundance of the genus Bacteroides and negatively correlated with Akkermansia. After the first week, the abundances of six phylogenetically diverse families (Peptococcaceae, S24‐7, Verrucomicrobiae, Anaeroplasmataceae, Streptococcaceae, Methanobacteriaceae) were associated with subsequent reductions in chick growth in an age‐specific and transient manner. These results have broad implications for our understanding of the development of gut microbiota and its associations with animal growth.

Hydrological Outlook UK: an operational streamflow and groundwater level forecasting system at monthly to seasonal time scales - Christel Prudhomme; Jamie Hannaford; Shaun Harrigan; David Boorman; Jeff Knight; Victoria Bell; Christopher Jackson; Cecilia Svensson; Simon Parry; Nuria Bachiller-Jareno; Helen Davies; Richard Davis; et al. (Hydrological Sciences Journal, 2017)

Transcriptional characterization of Vibrio fischeri during colonization of juvenile Euprymna scolopes - Luke R. Thompson; Kiel Nikolakakis; Shu Pan; Jennifer Reed; Rob Knight; Edward G. Ruby (Environmental Microbiology, 2017)
Summary The marine bacterium Vibrio fischeri is the monospecific symbiont of the Hawaiian bobtail squid, Euprymna scolopes , and the establishment of this association involves a number of signaling pathways and transcriptional responses between both partners. We report here the first full RNA‐Seq dataset representing host‐associated V. fischeri cells from colonized juvenile E. scolopes , as well as comparative transcriptomes under both laboratory and simulated marine planktonic conditions. These data elucidate the broad transcriptional changes that these bacteria undergo during the early stages of symbiotic colonization. We report several previously undescribed and unexpected transcriptional responses within the early stages of this symbiosis, including gene expression patterns consistent with biochemical stresses inside the host, and metabolic patterns distinct from those reported in associations with adult animals. Integration of these transcriptional data with a recently developed metabolic model of V. fischeri provides us with a clearer picture of the metabolic state of symbionts within the juvenile host, including their possible carbon sources. Taken together, these results expand our understanding of the early stages of the squid–vibrio symbiosis, and more generally inform the transcriptional responses underlying the activities of marine microbes during host colonization.

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Phylogenetic and ecological factors impact the gut microbiota of two Neotropical primate species - Katherine R. Amato; Rodolfo Martinez-Mota; Nicoletta Righini; Melissa Raguet-Schofield; Fabiana Paola Corcione; Elisabetta Marini; Greg Humphrey; Grant Gogul; James Gaffney; Elijah Lovelace; LaShanda Williams; Albert Luong; et al. (Oecologia, 2016)

Identifying qualitative effects of different grazing types on below‐ground communities and function in a long‐term field experiment - Catriona A. Macdonald; Michael J. Crawley; Denis J. Wright; Justin Kuczynski; Lucinda Robinson; Rob Knight; Waleed Abu Al‐Soud; Søren J. Sørensen; Ye Deng; Jizhong Zhou; Brajesh K. Singh (Environmental Microbiology, 2015)
Summary Herbivory is an important modulator of plant biodiversity and productivity in grasslands, but our understanding of herbivore‐induced changes on below‐ground processes and communities is limited. Using a long‐term (17 years) experimental site, we evaluated impacts of rabbit and invertebrate grazers on some soil functions involved in carbon cycling, microbial diversity, structure and functional composition. Both rabbit and invertebrate grazing impacted soil functions and microbial community structure. All functional community measures (functions, biogeochemical cycling genes, network association between different taxa) were more strongly affected by invertebrate grazers than rabbits. Furthermore, our results suggest that exclusion of invertebrate grazers decreases both microbial biomass and abundance of genes associated with key biogeochemical cycles, and could thus have long‐term consequences for ecosystem functions. The mechanism behind these impacts are likely to be driven by both direct effects of grazing altering the pattern of nutrient inputs and by indirect effects through changes in plant species composition. However, we could not entirely discount that the pesticide used to exclude invertebrates may have affected some microbial community measures. Nevertheless, our work illustrates that human activity that affects grazing intensity may affect ecosystem functioning and sustainability, as regulated by multi‐trophic interactions between above‐ and below‐ground communities.

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Major H istocompatibility C omplex class II b polymorphism influences gut microbiota composition and diversity - Daniel I. Bolnick; Lisa K. Snowberg; J. Gregory Caporaso; Chris Lauber; Rob Knight; William E. Stutz (Molecular Ecology, 2014)
Animals harbour diverse communities of symbiotic bacteria, which differ dramatically among host individuals. This heterogeneity poses an immunological challenge: distinguishing between mutualistic and pathogenic members of diverse and host‐specific microbial communities. We propose that M ajor H istocompatibility class II ( MHC ) genotypes contribute to recognition and regulation of gut microbes, and thus, MHC polymorphism contributes to microbial variation among hosts. Here, we show that MHC II b polymorphism is associated with among‐individual variation in gut microbiota within a single wild vertebrate population of a small fish, the threespine stickleback. We sampled stickleback from C edar L ake, on V ancouver I sland, and used next‐generation sequencing to genotype the sticklebacks’ gut microbiota (16S sequencing) and their MHC class II b exon 2 sequences. The presence of certain MHC motifs was associated with altered relative abundance (increase or decrease) of some microbial Families. The effect sizes are modest and entail a minority of microbial taxa, but these results represent the first indication that MHC genotype may affect gut microbiota composition in natural populations ( MHC ‐microbe associations have also been found in a few studies of lab mice). Surprisingly, these MHC effects were frequently sex‐dependent. Finally, hosts with more diverse MHC motifs had less diverse gut microbiota. One implication is that MHC might influence the efficacy of therapeutic strategies to treat dysbiosis‐associated disease, including the outcome of microbial transplants between healthy and diseased patients. We also speculate that macroparasite‐driven selection on MHC has the potential to indirectly alter the host gut microbiota, and vice versa.

Individuals' diet diversity influences gut microbial diversity in two freshwater fish (threespine stickleback and Eurasian perch) - Daniel I. Bolnick; Lisa K. Snowberg; Philipp E. Hirsch; Christian L. Lauber; Rob Knight; J. Gregory Caporaso; Richard Svanbäck (Ecology Letters, 2014)
Vertebrates' diets profoundly influence the composition of symbiotic gut microbial communities. Studies documenting diet‐microbiota associations typically focus on univariate or categorical diet variables. However, in nature individuals often consume diverse combinations of foods. If diet components act independently, each providing distinct microbial colonists or nutrients, we expect a positive relationship between diet diversity and microbial diversity. We tested this prediction within each of two fish species (stickleback and perch), in which individuals vary in their propensity to eat littoral or pelagic invertebrates or mixtures of both prey. Unexpectedly, in most cases individuals with more generalised diets had less diverse microbiota than dietary specialists, in both natural and laboratory populations. This negative association between diet diversity and microbial diversity was small but significant, and most apparent after accounting for complex interactions between sex, size and diet. Our results suggest that multiple diet components can interact non‐additively to influence gut microbial diversity.

The amphibian skin‐associated microbiome across species, space and life history stages - Jordan G. Kueneman; Laura Wegener Parfrey; Douglas C. Woodhams; Holly M. Archer; Rob Knight; Valerie J. McKenzie (Molecular Ecology, 2014)
Skin‐associated bacteria of amphibians are increasingly recognized for their role in defence against pathogens, yet we have little understanding of their basic ecology. Here, we use high‐throughput 16 S r RNA gene sequencing to examine the host and environmental influences on the skin microbiota of the cohabiting amphibian species A naxyrus boreas, P seudacris regilla, T aricha torosa and L ithobates catesbeianus from the C entral V alley in C alifornia. We also studied populations of R ana cascadae over a large geographic range in the K lamath M ountain range of N orthern C alifornia, and across developmental stages within a single site. Dominant bacterial phylotypes on amphibian skin included taxa from B acteroidetes, G ammaproteobacteria, A lphaproteobacteria, F irmicutes, S phingobacteria and A ctinobacteria. Amphibian species identity was the strongest predictor of microbial community composition. Secondarily, within a given amphibian species, wetland site explained significant variation. Amphibian‐associated microbiota differed systematically from microbial assemblages in their environments. Rana cascadae tadpoles have skin bacterial communities distinct from postmetamorphic conspecifics, indicating a strong developmental shift in the skin microbes following metamorphosis. Establishing patterns observed in the skin microbiota of wild amphibians and environmental factors that underlie them is necessary to understand skin symbiont community assembly, and ultimately, the role skin microbiota play in the extended host phenotype including disease resistance.

Convergence of gut microbiomes in myrmecophagous mammals - Frédéric Delsuc; Jessica L. Metcalf; Laura Wegener Parfrey; Se Jin Song; Antonio González; Rob Knight (Molecular Ecology, 2014)
Mammals have diversified into many dietary niches. Specialized myrmecophagous (ant‐ and termite‐eating) placental mammals represent a textbook example of evolutionary convergence driven by extreme diet specialization. Armadillos, anteaters, aardvarks, pangolins and aardwolves thus provide a model system for understanding the potential role of gut microbiota in the convergent adaptation to myrmecophagy. Here, we expand upon previous mammalian gut microbiome studies by using high‐throughput barcoded I llumina sequencing of the 16S r RNA gene to characterize the composition of gut microbiota in 15 species representing all placental myrmecophagous lineages and their close relatives from zoo‐ and field‐collected samples. We confirm that both diet and phylogeny drive the evolution of mammalian gut microbiota, with cases of convergence in global composition, but also examples of phylogenetic inertia. Our results reveal specialized placental myrmecophages as a spectacular case of large‐scale convergence in gut microbiome composition. Indeed, neighbour‐net networks and beta‐diversity plots based on U ni F rac distances show significant clustering of myrmecophagous species (anteaters, aardvarks and aardwolves), even though they belong to phylogenetically distant lineages representing different orders. The aardwolf, which diverged from carnivorous hyenas only in the last 10 million years, experienced a convergent shift in the composition of its gut microbiome to become more similar to other myrmecophages. These results confirm diet adaptation to be a major driving factor of convergence in gut microbiome composition over evolutionary timescales. This study sets the scene for future metagenomic studies aiming at evaluating potential convergence in functional gene content in the microbiomes of specialized mammalian myrmecophages.

Diversity, distribution and sources of bacteria in residential kitchens - Gilberto E. Flores; Scott T. Bates; J. Gregory Caporaso; Christian L. Lauber; Jonathan W. Leff; Rob Knight; Noah Fierer (Environmental Microbiology, 2013)
Summary Bacteria readily colonize kitchen surfaces, and the exchange of microbes between humans and the kitchen environment can impact human health. However, we have a limited understanding of the overall diversity of these communities, how they differ across surfaces and sources of bacteria to kitchen surfaces. Here we used high‐throughput sequencing of the 16 S rRNA gene to explore biogeographical patterns of bacteria across > 80 surfaces within the kitchens of each of four households. In total, 34 bacterial and two archaeal phyla were identified, with most sequences belonging to the A ctinobacteria , B acteroidetes , F irmicutes and P roteobacteria . Genera known to contain common food‐borne pathogens were low in abundance but broadly distributed throughout the kitchens, with different taxa exhibiting distinct distribution patterns. The most diverse communities were associated with infrequently cleaned surfaces such as fans above stoves, refrigerator/freezer door seals and floors. In contrast, the least diverse communities were observed in and around sinks, which were dominated by biofilm‐forming G ram‐negative lineages. Community composition was influenced by conditions on individual surfaces, usage patterns and dispersal from source environments. Human skin was the primary source of bacteria across all kitchen surfaces, with contributions from food and faucet water dominating in a few specific locations. This study demonstrates that diverse bacterial communities are widely distributed in residential kitchens and that the composition of these communities is often predictable. These results also illustrate the ease with which human‐ and food‐associated bacteria can be transferred in residential settings to kitchen surfaces.

Geographic distance and pH drive bacterial distribution in alkaline lake sediments across Tibetan Plateau - Jinbo Xiong; Yongqin Liu; Xiangui Lin; Huayong Zhang; Jun Zeng; Juzhi Hou; Yongping Yang; Tandong Yao; Rob Knight; Haiyan Chu (Environmental Microbiology, 2012)
Summary Continent‐scale biogeography has been extensively studied in soils and marine systems, but little is known about biogeographical patterns in non‐marine sediments. We used barcode pyrosequencing to quantify the effects of local geochemical properties and geographic distance for bacterial community structure and membership, using sediment samples from 15 lakes on the Tibetan Plateau (4–1670 km apart). Bacterial communities were surprisingly diverse, and distinct from soil communities. Four of 26 phyla detected were dominant: Proteobacteria , Bacteroidetes , Firmicutes and Actinobacteria , albeit 20.2% of sequences were unclassified at the phylum level. As previously observed in acidic soil, pH was the dominant factor influencing alkaline sediment community structure, phylotype richness and phylogenetic diversity. In contrast, archaeal communities were less affected by pH. More geographically distant sites had more dissimilar communities ( r = 0.443, P = 0.030). Variance partitioning analysis showed that geographic distance (historical contingencies) contributed more to bacterial community variation (12.2%) than any other factor, although the environmental factors explained more variance when combined (28.9%). Together, our results show that pH is the best predictor of bacterial community structure in alkaline sediments, and confirm that both geographic distance and chemical factors govern bacterial biogeography in lake sediments.

Environmental and ecological factors that shape the gut bacterial communities of fish: a meta‐analysis - KAREN E. SULLAM; STEVEN D. ESSINGER; CATHERINE A. LOZUPONE; MICHAEL P. O’CONNOR; GAIL L. ROSEN; ROB KNIGHT; SUSAN S. KILHAM; JACOB A. RUSSELL (Molecular Ecology, 2012)
Symbiotic bacteria often help their hosts acquire nutrients from their diet, showing trends of co‐evolution and independent acquisition by hosts from the same trophic levels. While these trends hint at important roles for biotic factors, the effects of the abiotic environment on symbiotic community composition remain comparably understudied. In this investigation, we examined the influence of abiotic and biotic factors on the gut bacterial communities of fish from different taxa, trophic levels and habitats. Phylogenetic and statistical analyses of 25 16S rRNA libraries revealed that salinity, trophic level and possibly host phylogeny shape the composition of fish gut bacteria. When analysed alongside bacterial communities from other environments, fish gut communities typically clustered with gut communities from mammals and insects. Similar consideration of individual phylotypes (vs. communities) revealed evolutionary ties between fish gut microbes and symbionts of animals, as many of the bacteria from the guts of herbivorous fish were closely related to those from mammals. Our results indicate that fish harbour more specialized gut communities than previously recognized. They also highlight a trend of convergent acquisition of similar bacterial communities by fish and mammals, raising the possibility that fish were the first to evolve symbioses resembling those found among extant gut fermenting mammals.

Global patterns in the biogeography of bacterial taxa - Diana R. Nemergut; Elizabeth K. Costello; Micah Hamady; Catherine Lozupone; Lin Jiang; Steven K. Schmidt; Noah Fierer; Alan R. Townsend; Cory C. Cleveland; Lee Stanish; Rob Knight (Environmental Microbiology, 2011)
Summary Bacteria control major nutrient cycles and directly influence plant, animal and human health. However, we know relatively little about the forces shaping their large‐scale ecological ranges. Here, we reveal patterns in the distribution of individual bacterial taxa at multiple levels of phylogenetic resolution within and between Earth's major habitat types. Our analyses suggest that while macro‐scale habitats structure bacterial distribution to some degree, abundant bacteria (i.e. detectable using 16S rRNA gene sequencing methods) are confined to single assemblages. Additionally, we show that the most cosmopolitan taxa are also the most abundant in individual assemblages. These results add to the growing body of data that support that the diversity of the overall bacterial metagenome is tremendous. The mechanisms governing microbial distribution remain poorly understood, but our analyses provide a framework with which to test the importance of macro‐ecological environmental gradients, relative abundance, neutral processes and the ecological strategies of individual taxa in structuring microbial communities.

Consistent effects of nitrogen fertilization on soil bacterial communities in contrasting systems - Kelly S. Ramirez; Christian L. Lauber; Rob Knight; Mark A. Bradford; Noah Fierer (Ecology, 2010)
Ecosystems worldwide are receiving increasing amounts of reactive nitrogen (N) through anthropogenic activities. Although the effects of increased N inputs on plant communities have been reasonably well studied, few comparable studies have examined impacts on whole soil bacterial communities, though they play critical roles in ecosystem functioning. We sampled soils from two long‐term ecological research (LTER) experimental N gradients, both of which have been amended with NH 4 NO 3 ; a grassland at Cedar Creek (27 years of N additions) and an agricultural field at Kellogg Biological Station (8 years of N additions). By examining shifts in bacterial communities across these contrasting ecosystem types, we could test competing hypotheses about the direct and indirect factors that might drive bacterial responses to elevated N inputs. Bacterial community structure was highly responsive to N additions. We observed predictable and consistent changes in the structure of the bacterial communities across both ecosystem types. Our results suggest that bacterial communities across these gradients are more structured by N and/or soil carbon availability than by shifts in the plant community or soil pH associated with the elevated nitrogen inputs. In contrast to the pronounced shifts in bacterial community composition and in direct contrast to the patterns often observed in plant communities, increases in N availability did not have consistent effects on the richness and diversity of soil bacterial communities.

The ecology of the phyllosphere: geographic and phylogenetic variability in the distribution of bacteria on tree leaves - Amanda J. Redford; Robert M. Bowers; Rob Knight; Yan Linhart; Noah Fierer (Environmental Microbiology, 2010)
Summary Large populations of bacteria live on leaf surfaces and these phyllosphere bacteria can have important effects on plant health. However, we currently have a limited understanding of bacterial diversity on tree leaves and the inter‐ and intra‐specific variability in phyllosphere community structure. We used a barcoded pyrosequencing technique to characterize the bacterial communities from leaves of 56 tree species in Boulder, Colorado, USA, quantifying the intra‐ and inter‐individual variability in the bacterial communities from 10 of these species. We also examined the geographic variability in phyllosphere communities on Pinus ponderosa from several locations across the globe. Individual tree species harboured high levels of bacterial diversity and there was considerable variability in community composition between trees. The bacterial communities were organized in patterns predictable from the relatedness of the trees as there was significant correspondence between tree phylogeny and bacterial community phylogeny. Inter‐specific variability in bacterial community composition exceeded intra‐specific variability, a pattern that held even across continents where we observed minimal geographic differentiation in the bacterial communities on P. ponderosa needles.

Soil bacterial diversity in the Arctic is not fundamentally different from that found in other biomes - Haiyan Chu; Noah Fierer; Christian L. Lauber; J. G. Caporaso; Rob Knight; Paul Grogan (Environmental Microbiology, 2010)
Summary The severe environmental stresses of the Arctic may have promoted unique soil bacterial communities compared with those found in lower latitude environments. Here, we present a comprehensive analysis of the biogeography of soil bacterial communities in the Arctic using a high resolution bar‐coded pyrosequencing technique. We also compared arctic soils with soils from a wide range of more temperate biomes to characterize variability in soil bacterial communities across the globe. We show that arctic soil bacterial community composition and diversity are structured according to local variation in soil pH rather than geographical proximity to neighboring sites, suggesting that local environmental heterogeneity is far more important than dispersal limitation in determining community‐level differences. Furthermore, bacterial community composition had similar levels of variability, richness and phylogenetic diversity within arctic soils as across soils from a wide range of lower latitudes, strongly suggesting a common diversity structure within soil bacterial communities around the globe. These results contrast with the well‐established latitudinal gradients in animal and plant diversity, suggesting that the controls on bacterial community distributions are fundamentally different from those observed for macro‐organisms and that our biome definitions are not useful for predicting variability in soil bacterial communities across the globe.

RNA–Amino Acid Binding: A Stereochemical Era for the Genetic Code - Michael Yarus; Jeremy Joseph Widmann; Rob Knight (Journal of Molecular Evolution, 2009)

The human microbiome: eliminating the biomedical/environmental dichotomy in microbial ecology - Ruth E. Ley; Rob Knight; Jeffrey I. Gordon (Environmental Microbiology, 2007)

Error Minimization and Coding Triplet/Binding Site Associations Are Independent Features of the Canonical Genetic Code - J. Gregory Caporaso; Michael Yarus; Rob Knight (Journal of Molecular Evolution, 2005)

tRNA Creation by Hairpin Duplication - Jeremy Widmann; Massimo Di Giulio; Michael Yarus; Rob Knight (Journal of Molecular Evolution, 2005)